2008
DOI: 10.1145/1352322.1352222
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate data communications and networking projects using opnet and wireshark software

Abstract: The national importance of creating "content reflecting cutting edge developments in STEM fields" has been recognized the National Science Foundation. The National Research Council has also noted that creating engaging laboratory and classroom experiences is a challenge to effective undergraduate education in STEM disciplines. In this paper we present our endeavors to address these issues in the field of computer networks. We discuss our experiences with novel laboratory and classroom projects using OPNET and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Ethereal, a publicdomain protocol analyzer now known as Wireshark [8], is used in this unit to capture and examine packets. Other work on using protocol analyzers in networking courses can be found in [1][2][3][4].…”
Section: The Resulting Changesmentioning
confidence: 99%
“…Ethereal, a publicdomain protocol analyzer now known as Wireshark [8], is used in this unit to capture and examine packets. Other work on using protocol analyzers in networking courses can be found in [1][2][3][4].…”
Section: The Resulting Changesmentioning
confidence: 99%
“…Panko(2017),twelveonlinelabassignmentshavebeendesignedandoffered tostudentsforexploringtheEthernet,TokenRing,SwitchedLocalAreaNetworks(LANs),Frame Relay(FR),AsynchronousTransferMode(ATM),RoutingInformationProtocol(RIP),OpenShortest PathFirst(OSPF)protocol,TransmissionControlProtocol(TCP),QueuingDisciplines,Resource ReservationProtocol(RSVP),Firewalls,andVirtualPrivateNetworks(VPNs).Usingthisknowledge andskills,studentsdeveloptheirownlabprojects (Kumar,2005)andincludevirtuallabtechniques intotheirresearchprojects (Sood,2007)whichinvolvevariousnetworkapplicationprotocols,such asFileTransferProtocol(FTP),SimpleNetworkManagementProtocol(SNMP),andSimpleMail TransferProtocol(SMTP) (Riabov,2006b). Hnatyshin and Lobo (2008) have recently published an overview of undergraduate data communicationsandnetworkingprojectsthatuseOPNETandWireshark(2017)software.Confirming our experience, they have also found that these labs help undergraduate students understand fundamentalnetworkingconceptsthroughmodelingandsimulationofcomputingsystems.…”
Section: Data Communication In Networking Systemsmentioning
confidence: 99%
“…Given the simplicity of instrumenting entirely text-based tools, like a command line, we undertake the instrumentation of a graphical tool that issues text queries, Traffic Circle [11], and a graphical tool that allows extension to its selection model, Wireshark [12] [13], as an exemplar of the former of the two interaction considerations.…”
Section: Instrumentationmentioning
confidence: 99%